Ethnobotanical review and pharmacological properties of selected medicinal plants in Brunei Darussalam: Litsea elliptica, Dillenia suffruticosa, Dillenia excelsa, Aidia racemosa, Vitex pinnata and Senna alata - May Poh Yik Goh; Aida Maryam Basri; Hartini Yasin; Hussein Taha; Norhayati Ahmad (Asian Pacific Journal of Tropical Biomedicine, 2017)
The aim of the current study is to review the medicinal properties of the plants found in Brunei Darussalam namely Litsea elliptica, Dillenia suffruticosa, Dillenia excelsa, Aidia racemosa, Vitex pinnata and Senna alata. The known phytochemical constituents of these plants and their ability to bring about a range of biological activities are included in this review. These plants have been used traditionally for a multitude of diseases and illnesses. There is a lot of untapped potential in these medicinal plants which could cure multiple diseases.